Lactic Acid Fermentation of Minced Meat of Leiognathus splendens (Cuvier, 1829) using Different Bacterial Sources - N., Neethiselvan; G., Indra Jasmine; G., Jeyasekeran (Fishery Technology, 2025)
Fermentation of minced meat of silverbelly Leiognathus splendens (Cuvier, 1829) using three different lactic acid bacterial sources viz. pure culture of Lactobacillus plantarum, fermented cabbage and curd revealed fermented cabbage as the ideal source of lactic acid bacteria for the preservation of fish meat through lactic acid fermentation. 48h fermented cabbage could bring down the pH of the minced meat mixture to 4.4 within 48 h of fermentation whereas the other two minced meat mixtures took nearly 84 h to reach the same pH. Fermented cabbage can also be easily prepared and maintained for fermenting fish meat on commercial scale. Free sugar, lactic acid content, NPN, TVBN and lactic acid bacterial count were found to be good indices of quality of the fermented product under storage.